Attention arbitrators, things are changing in the construction sector!: Building Information Modelling (BIM) as evidence in arbitration - Giles Ponce, Carlos (2025)
Building Information Modelling (BIM) is essential for orderly project management. Linked to international standardized construction contracts such as NEC (New Engineering Contracts), it contributes to the reduction of execution times and project cost savings, which, in public works, translates into a more efficient management of government resources. By concentrating information that is provided contemporaneously by all parties involved, it will contribute to generate in the arbitrators the conviction they require with a view to reaching material truth, thus contributing to a more solid motivation of the awards. This poses the challenge for arbitrators to become more skilled in the technical and technological aspects of construction disputes, in general, and in the technical evaluation of evidence, in particular.